EXPLORING STUDENTS’ EXPECTATIONS AND REALITIES OF GROUP WORK IN EFL LEARNING: A QUALITATIVE CASE STUDY - Adieli Laoli; Gulo, Dari Hati; Friska Putri Waruwu; Efen Ronalis Lase; Hendrikus Agusman Lature (Widya Mandala Surabaya Catholic University, 2026)
This study explores third-semester students’ expectations and actual experiences of group work in English as a Foreign Language (EFL) learning within an English Education Study Program in higher education. Employing a qualitative descriptive case study design, the research involved ten third-semester students (five males and five females) selected through purposive sampling based on their prior experience with collaborative learning. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings reveal that most participants held positive expectations of group work, particularly regarding increased confidence, reduced anxiety, and greater engagement in English learning. These expectations were largely confirmed in practice, indicating an alignment between students’ expectations and classroom realities at the affective level. However, the study also identified important tensions, as unequal participation and inconsistent use of English persisted during group interactions. While group work functioned as an effective scaffold that encouraged participation, it did not automatically ensure equitable contribution or sustained target-language use. By explicitly contrasting students’ expectations with their lived classroom experiences, this study contributes to a more nuanced understanding of group work as a pedagogical strategy whose effectiveness depends on structured design and teacher scaffolding. The findings offer important implications for EFL teacher education and collaborative learning practices in higher education.